Functional Non‐Volatile Memory Devices: From Fundamentals to Photo‐Tunable Properties. Issue 5 (7th February 2019) - Wang, Zhanpeng; Zhang, Shi‐Rui; Zhou, Li; Mao, Jing‐Yu; Han, Su‐Ting; Ren, Yi; Yang, Jia‐Qin; Wang, Yan; Zhai, Yongbiao; Zhou, Ye
Abstract : As one of the five basic components in a modern computer system, memory plays a key role in data storage while the Von Neumann architecture still occupies a principal position in modern digital era. With the rapid development of portable electronic devices, non‐volatile memories are of great importance in human's daily life. High‐performance memory devices are highly demanded, and novel materials applied to flash memory and resistive random access memory (ReRAM) have been widely investigated. The functionalities of memories can be broadened with the development of semiconductor technologies. As a facile and low‐power electromagnetic wave, light can be another modulation medium, which will not bring destructive operation and can enhance the device performance. In this review, the focus is on flash memory and ReRAM based on various functional materials as well as the recent development of photo‐tunable memories. Abstract : In this review, several kinds of materials for non‐volatile memories as well as the photo‐tunable properties of memories will be introduced. Novel materials applied to flash memory and resistive random access memory (ReRAM) have been widely investigated. As a facile and low‐power electromagnetic wave, light is chosen as another modulation medium which will not bring destructive operation and can enhance the device performance.